The Brainliest Answer!

This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Please refer to the image
1 5 1
I will srnd u in inbox
As there is no edit option available
k f9
a very big thankzz 2 u
U r welcome my friend !!!! :)
Let p(x)=If 2 x^{4}-3 x^{3}+5 x^{2}-4x-3 and
If p(x) is divided by g(x),
Then by remainder theorem,
Remainder=p(2) {since p(x)=0, p(x)=x-2 ⇒x=2}